MANAJEMEN DANA WAKAF TUNAI UNTUK PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM (Studi pada BMH Cabang Malang) - Djalaludin, Ahmad; Maisyaroh, Maisyaroh (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
Researcher was interested in conducting research in the Baitul Maal Hidayatullah Branch Malang with the aim to identify management of funds cash waqaf in these institutions and the general problem and the steps taken by BMH Branch Malang in overcoming these problems. This research is a qualitative with descriptive approach. The techniques used in data collection methods are observation, interview and documentation. The survey revealed that the funds cash waqaf collected by the BMH branch Malang targeted specifically for the education program for the development of Islamic educational institutions Ar-Rohmah for girls which is located in Dau Malang. The forms of development such as land acquisition in the vicinity/area of that institution. The main constraint in this management of cash fund of wakaf is the human resources/employees who are less optimal in performing his duties and it is difficult to be taken to develop the organization. To overcome this, the BMH branch Malang creates training initiatives in order to motivate their employees. Â